Development of Interactive-Based Learning Modules on Main Idea Material to Improve Reading Comprehension Skills of Grade IV Elementary School Students - Pipi Andriani; Mardianto; Pangulu Abdul Karim (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The purpose of this study is to develop a valid, practical, and effective interactive learning module in the main idea material. The type of research conducted is development research or commonly known as Research and Development (R&D). This research methodology uses the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The population of this study was 20 fourth-grade students. Data collection instruments in the study used validation sheets, questionnaires, and tests. Data collection techniques in the study were by testing the validity of two validators, testing the practicality, and testing the effectiveness using normalized values (N-Gain). The results of this study indicate that: (1) The interactive-based learning module was declared "Very Valid" after going through a validation process by media experts with a percentage of 94.3% (Very Valid) and by material experts with a percentage of 80% (Valid), (2) the interactive-based learning module was declared "Very Practical" based on the results of trials by educators with a percentage of 98.4% and by students with a percentage of 100%, and (3) the interactive-based learning module was proven to be "Very Effective" in improving students' reading comprehension skills by obtaining a normalized gain value of 0.82, which is in the high category.